9514 1404 393
Answer:
(-8, -8)
Explanation:
We notice that the coefficients of y are +4 and -4, so have a sum of zero. This means we can add the two equations to eliminate the y-terms.
(-7x +4y) +(4x -4y) = (24) +(0)
-3x = 24 . . . . . . . . . simplify
x = -8 . . . . . . . . . . . divide both sides by -3
Now, we can find y using either equation.
4(-8) -4y = 0
-8 -y = 0 . . . . . . . . divide both sides by 4
-8 = y . . . . . . . . . . add y to both sides
The solution to the system of equations is ...
(x, y) = (-8, -8)